ENVIRONMENTAL FACTORS OF THE HOME AFFECT THE DENSITY OF AEDES AEGYPTI (DIPTERA: CULICIDAE) - Satoto, Tri Baskoro Tunggul; Diptyanusa, Ajib; Setiawan, Yohanes Didik; Alvira, Nur (Lembaga Penelitian Universitas YARSI, 2017)
The transmission of Dengue Hemorrhagic Fever (DHF) by Aedes aegypti and Aedes albopictus mosquitoes is influenced by climate change and several environmental factors, namely light intensity, CO2, temperature, humidity, housing condition, drainage, and vegetation. This study aims to identify the relationship between environmental factors and dengue vector population density. This research applies an observational analytic study with a cross-sectional design. The study was conducted in 2012, in the city of Yogyakarta, Indonesia, in 39 houses in the Kricak Village and in 50 houses in the Prenggan Village. Data were collected by observation, interview, and completing checklists, as well as by measuring environmental variables. The differential effect of various factors influencing mosquito density was tested using an independent sample t-test for physical environmental factors and chi-square test for the variable physical condition of the house, biologically relevant environmental factors, drainage, residential density, and the distance between houses. The probability value was p 0.05. The results showed that differences in the physical environment, the physical condition of the house, residential density, and vegetation, all affect the density of dengue vector mosquitoes in the villages of Kricak and Prenggan. The need of raising public awareness about healthy living and care for the environment, along with advocacy to stakeholders, is important for vector density control.